Dimensions of Citizenship: Associations among Adolescents' Sociopolitical Values and Civic Judgments. Issue 2 (14th April 2014) - Metzger, Aaron; Oosterhoff, Benjamin; Palmer, Cara A.; Ferris, Kaitlyn
ABSTRACT This study used a sample of 467 middle and high school students (Mage = 15.26) from a mid-Atlantic state. Structural equation models controlling for demographic variables (age, gender, and parents' education) examined associations between three developing sociopolitical values (spiritualty, patriotism, and authoritarianism) and adolescents' social and moral judgments (obligation and social praise) concerning four civic activities (community service, standard political involvement, social movement, and community gathering). Spirituality was associated with judgments for community service and community gathering involvement while authoritarian values were associated with the prioritization of all forms of civic activity. Multigroup analyses indicated that associations between authoritarianism and both community service and social movement judgments were stronger for younger adolescents while spirituality was more strongly associated with community service judgments for older adolescents. Patriotic beliefs were associated with civic judgments for children of college-educated parents, but not children of noncollege-educated parents.